STRATEGIES ADOPTED BY THE ADVENTIST CENTRE IN ENHANCING LIVELIHOOD SUSTAINABILITY AMONG BENEFICIARIES IN KIBAGARE SLUM - ongere, isabella (Advances in Social Sciences Research Journal, 2019)
A livelihood strategy is an organized set of lifestyle choices, goals and values, and activities which Non Governmental Organizations are allowed a flexibility to adopt in order to built and improve livelihoods. Inspite of well documented NGO interventions towards the improvement of livelihoods of urban slum populations, effects of these projects are hardly felt after their exit. It is against this background that this paper addresses the livelihood strategies adopted by Adventist Centre to enhance livelihood sustainability among beneficiaries. The study involved 105 beneficiaries and 10 key informants selected by probability and non probability sampling method. Primary data was collected from the beneficiaries through interviews and questionnaires while secondary data was collected from the AC records such as minutes, policy documents, donor agency correspondencies, operating manual/procedures, grant approval procedures and memorandums of approval. This paper addresses the findings of this research conducted by the author at Kibagare slum, in Nairobi county, Kenya. It discusses the strategies adopted by AC, factors that affect the strategies and the strategies that were most effective and finally recommends on effective ways strategies should be adopted. Recommendations on how to ensure strategies covered all the elements that contribute to sustainable livelihoods that AC needed to develop were recommended.